Modified Technology Acceptance Model As A Predictor Of Online Purchase Behavior: A Malaysian Perspective - Chew, Kok Wai (2007)
This study attempted to answer the question: Can the Modified Technology Acceptance Model (TAM) explain online purchase behavior of Malaysian consumers? The research objectives were to: (a) investigate the effects of conventional TAM constructs such as perceived usefulness, perceived ease of use, attitude, and behavioral intention on online purchase behavior; (b) determine additionally the influence of different types of risks on online purchase behavior; (c) find out the role that trust in online companies and the trust in Internet security technology play in impacting online purchase behavior; (d) explore the significance of anxiety in affecting online purchase behavior; and finally (e) find out the role of perceived convenience in influencing online purchase behavior.